Pediatric Dermatology and Internet. An update. - Cutrone, M. (European Journal of Pediatric Dermatology, 2009)
Pediatricians and dermatologists should always more frequently use the web and get out the best from the latter, this way protecting their patients from the excessive do-it-yourself informations. This article puts in evidence some functions of the net, which can be used by all physicians.